Associação do Polimorfismo 14pb ins/del do gene Hla-G com a endometriose em mulheres de Mato Grosso-Brasil - Seidel, Joziane Agnoria da Silva (2015)
Endometriosis is a nosological condition characterized by the presence of functional tissue similar to eutopic endometrium in pelvic peritoneum, ovaries, rectovaginal septum. Its prevalence in infertile women varies between 30 and 50%. The clinical manifestations are variable, including deep dyspareunia, disabling dysmenorrhea, chronic pelvic pain and infertility. The influence of genes involved in the immune system and its variants have been investigated for their susceptibility and progression of endometriosis. The gene of human leukocyte antigen-G (HLA-G) belongs to the main histocompatibility complex class I. It´s mapped on 6p21, has eight exons and seven introns being translated region where polymorphism is present 14pb insertion/deletion (ins/del). This study aims to identify possible association between the polymorphism 14pb ins/del in HLA-G gene and endometriosis in women of Mato Grosso-Brazil. The epidemiological design is observational case-control type. 349 women were included (209 cases and 140 controls) aged 16-50 years, seen and diagnosed by laparoscopy in a human reproduction center of Mato Grosso. Interviews and collection of peripheral blood samples were performed for each participant. DNA was extracted by salting out method, polymerase chain reaction using specific primers, was performed and the fragments were visualized on 10% polyacrylamide gel. The genotypic and allelic frequencies of polymorphism 14pb ins/del HLA-G gene between cases and controls were observed more heterozygous genotypes ins/del 111 (53.1%) and 69 (49.3%) and alleles del 249 (59, 6%), 151 (54.0%), respectively. As regards staging, the genotypic frequencies ins/del grade I were 28 (58.3%); grade II, 36 (46.2%); grade III, 21 (48.8%) and grade IV, 26 (65.0%). The allelic frequencies del grade I were 54 (56.3%); grade II, 98 (62.8%); grade III, 49 (57.0%) and grade IV, 48 (60.0%). There was no significant difference in any variable analyzed. As the evaluation of polymorphisms 14pb ins/del HLA-G gene in the clinical variables between cases with or without infertility, most often heterozygous genotypes obtained were ins/del in 88 (55.0%) patients with infertility and 23 (47.0%) patients without infertility. The allele del was observed in infertile woman with a frequency of 186 (58.1%) and in no infertile women showed frequency of 63 (51.7%). Analyzing women with endometriosis and who reported abortion or not, it was noted that heterozygous genotypes were more frequent. In women with abortion was the frequency of ins/del 13 (48.1%) and without abortion ins/del 98 (53.8%). The results were not statistically significant in all clinical variables p>0.5. Our study found that the polymorphism 14pb ins/del in HLA-G gene did not influence the susceptibility to endometriosis in women Mato Grosso - Brazil. The genotypic and allelic frequencies are not associated with the staging and/or severity of the disease, infertility and miscarriages.